Microfacies Analysis and Basin Development of Hartha Formation in East Baghdad Oil field, Central Iraq - Homadi, Bilal Jasim; Al-Zaidy, Aiad Ali Hussien (Iraqi Journal of Science, 2020)
The Hartha Formation is one of the important formations deposited during Late Campanian age.The present study deals with four boreholes (EB-53, 54, 55 and 56) within the East Baghdad oil field to diagnoses the microfacies and interpret the depositional environments.Six major microfacies were recognized in the succession of the Hartha Formation. Their characteristic grain types and depositional texture enabled the recognition of paleoenvironment. There are Orbitoides wackestone-packstone , Orbitoides - miliolid wackestone, Peloidal and Pellets - echinoderm wackestone to packstone, Peloidal wackestone to packstone, Pelletal wackestone to packstone, and Planktonic foraminifera wackestone-packstone.Four associations’ facies were recognized in this succession, which are shallow open marine, deep open marine, semi-resricted, and restricted. The distribution of these associations led to the recognition of three major depositional stages in the studied succession.The first stage is represented by the semi-restricted facies within the lower part of the Hartha Formation, which is characterized by Orbitoides - miliolid wackestone to the northwest direction and developed to shallow open marine and deep marine to the southeast direction. In the second stage, the sea level was rising to deposit the deep open marine facies represented by planktonic foraminifera wackestone-packstone microfacies above the semi-restricted facies ,where the succession became characterized by Peloidal and Pellets - echinoderm wackestone to packstone microfacies of restricted association. The third stage is represented by the continuation of sea level rise. This caused the building of carbonate ramp of Shiranish Formation above the shallow open marine of Hartha Formation with conformable surface.